A Review of the Indonesian Regulatory Policy on MSMEs and Cooperatives for Boosting Economic Potential towards the Industrial Revolution 4.0 - Koesrianti, Koesrianti; Tanega, Joseph (Faculty of Law, Universitas Padjadjaran, 2024)
The Indonesian government emphasizes the economic potentials of Indonesian micro, small, and medium enterprises (MSMEs) and cooperatives in the Industrial Revolution 0.4 by adopting regulations, policies, and programs that are MSME friendly. This study aims to review the optimization of MSMEs’ digital capability by examining the regulations, the policies, and the programs. It examines the regulatory framework that facilitates the digital MSMEs ecosystem work. Employing a cross-disciplinary approach within law and economics, this legal study adopts a descriptive design, using data from primary and secondary sources on the digitalization of MSMEs in Indonesia. The digital economy necessitates specific managing the adoption of Information Communication and Technology (ICT) across all businesses in Indonesia, including large enterprises, small enterprises, and micro businesses. This study argues that these government measures had a low impact on Indonesian MSMEs. This study concludes that sustainability government support in creating an inclusive digital economy of MSMEs is indispensable. The spirit of gotong royong, Indonesia's culture of community cooperation, should be leveraged to empower MSMEs. The absence of a centralized institution to coordinate policies and programs on the digitalization of MSMEs undermines the effectiveness of the national digital strategies for MSMEs. Indonesia’s plan to become the tenth-largest economy in the world by 2030 may remain unattainable without addressing the gap.